2017
DOI: 10.3847/1538-4357/aa960c
|View full text |Cite
|
Sign up to set email alerts
|

The Geometry of the Sagittarius Stream from Pan-STARRS1 3π RR Lyrae

Abstract: We present a comprehensive and precise description of the Sagittarius (Sgr) stellar stream's 3D geometry as traced by its old stellar population. This analysis draws on the sample of ∼44,000 RR Lyrae (RRab) stars from the Pan-STARRS1 (PS1) 3π survey, which is~80% complete and~90% pure within 80kpc, and extends to 120 kpc with a distance precision of~3%. A projection of RR Lyrae stars within <   |˜| B 9 of the Sgr stream's orbital plane reveals the morphology of both the leading and the trailing arms at ver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
91
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(112 citation statements)
references
References 60 publications
14
91
6
1
Order By: Relevance
“…Variable stars, and particularly RR Lyrae stars, are excellent tracers of extra-tidal material around disrupting galaxies. RR Lyrae stars, for example, trace the tidal tails of the Sagittarius dSph galaxy (e.g., Hernitschek et al 2017). Extra-tidal RR Lyrae stars have also been found in other satellites such as Carina (Vivas & Mateo 2013) and the Hercules UFD (Garling et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Variable stars, and particularly RR Lyrae stars, are excellent tracers of extra-tidal material around disrupting galaxies. RR Lyrae stars, for example, trace the tidal tails of the Sagittarius dSph galaxy (e.g., Hernitschek et al 2017). Extra-tidal RR Lyrae stars have also been found in other satellites such as Carina (Vivas & Mateo 2013) and the Hercules UFD (Garling et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the FoF groups with observations and simulations of Sgr (Law & Majewski 2010;Koposov et al 2012;Belokurov et al 2014;Dierickx & Loeb 2017;Hernitschek et al 2017), X19 identified 3028 Sgr stream members, including 2626 K-giants (including 102 suspected duplicate stars), 158 M-giants, and 224 BHBs, which is the largest spectroscopic sample obtained in the Sgr stream yet. In the next section, we will exhibit the Sgr members in detail, including spatial, kinematic, and abundance features.…”
Section: Integrals Of Motion and Friends-of-friends Algorithmmentioning
confidence: 99%
“…To do so, we apply the selection cuts described in Section 3.2, to geometrically excise such overdensities. The largest overdensities removed are the Sagittarius stream (we remove sources associated with the Sgr stream according to Hernitschek et al 2017), as well as the thick disk (we remove sources within <  | | b 10 ) and close to the Galactic center and the bulge (we remove sources within R gc 20 kpc). Showing the source density in three different distance bins shows major overdensities, as well as how excising such overdense regions affects the cleaned sample.…”
Section: Rrlmentioning
confidence: 99%